Systellaspis pellucida ... - Komai, Tomoyuki; Ohtsuka, Susumu; Yamaguchi, Shuhei; Nakaguchi, Kazumitsu (Zenodo, 2018)
Systellaspis pellucida (Filhol, 1884) [New Japanese name: Sukashi-toge-hiodoshi-ebi] Figs. 4, 5 Restricted synonymy: Acanthephyra pellucida Filhol, 1884: 144, 162 [type locality: North-East Atlantic, 26°20’N, 14°53’W, 782 m; lectotype designated by Crosnier & Forest (1973)]. Acanthephyra affinis Faxon, 1896: 162, pl. 2, figs. 1–3 [type locality: off Granada, 286 m]. Systellaspis lanceocaudata.— Balss 1925: 243, figs. 12, 13. Not Systellaspis lanceocaudata Spence Bate, 1888. Systellaspis affinis.— Calman 1939: 190.— Dennel 1940: 345, figs. 19–28, pl. 25, figs. 4, 5, pl. 26, figs. 1–6; Chace 1947: 39, fig. 3. Syetellaspis pellucida.— Crosnier & Forest 1973: 92, figs. 26c, 27c.— Chace 1986: 67, figs. 34m –o, 35g, h.— Chan & Yu 1986:— Crosnier 1987: 720, figs. 12, 13, 14a, b, 15.— Hanamura 1987: 25, fig. 9c–e; Hanamura & Evans 1994: 52.— Cardoso & Young 2005: 70, figs. 54–58.— Pequegnat & Wicksten 2006: 102.— Hayashi 2007: 77.— Poupin & Corbari 2016: 17, fig. 4g. Material examined. T/ ... : Published as part of Komai, Tomoyuki, Ohtsuka, Susumu, Yamaguchi, Shuhei & Nakaguchi, Kazumitsu, 2018, New records of six deep-sea caridean shrimps (Crustacea: Decapoda) from the Ryukyu Islands and its adjacent waters, southwestern Japan, pp. 114-128 in Zootaxa 4457 (1) on pages 117-120, DOI: 10.11646/zootaxa.4457.1.5, http://zenodo.org/record/1457611 ...